Scalable Community Outreach for AI Literacy and Future Ready Skills Evidence from Indonesia–Malaysia Collaboration - Susan Purnama; Mugi Puspita; Irfan Achmad Musadat; Agung Pramayuda; Immanuel David Martsinus Situmorang (International Journal Of Community Service, 2026)
This study aimed to strengthen students’ and the general public’s understanding of how artificial intelligence (AI) is reshaping work and to promote future-ready competencies, including strategic upskilling and reskilling. The community-service activity was delivered in Indonesia via a Zoom Meeting webinar on 28 November 2025 titled “Shaping the Future Workforce in the Age of Artificial Intelligence.” Content was prepared from key reports on AI and work. Participant registration and feedback were collected using Google Forms (Google LLC). The intervention included expert talks (industry practitioner and academic), moderated discussion, and Q&A. Evaluation used a post-webinar survey with 5 point Likert items and open-ended questions. Participants reported clearer awareness of AI-driven job changes, emerging roles, and the importance of data/AI literacy. Key themes were continuous learning, building practical portfolios, and responsible AI use (bias, privacy, and validating AI outputs). The findings rely on self-reported perceptions from a single webinar, without a pre–post test, objective skill measures, or long-term follow-up. This study offers a replicable, low-cost webinar model for workforce-readiness education and contributes to HR development and digital-talent training by translating AI trends into actionable, practical competency guidance for higher education and community partners.